ANALYSIS OF THE RELATIONSHIP OF THE WORK ENVIRONMENT AND JOB SATISFACTION OF NURSES IN REGIONAL HOSPITALS - Herman; Tutus Rully; Intan Fadillah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
A healthy and safe environment is essential, because a healthy and secure environment can make a person work quietly, and the results of work are expected to meet the established standards. Job satisfaction is one of the factors that influences the working environment. This research aims to determine the relationship between the work environment and the job satisfaction of nurses in regional general hospitals in Bogor City. This study uses a quantitative approach. Data were collected by distributing questionnaires to 80 respondents. The sampling technique for this research uses saturated sampling. The analysis technique for this research is descriptive analysis, correlation coefficients (Rank Spearman), coefficient of determination r2, and correlation coefficient hypothesis. This research shows a strong relationship between work environment and job satisfaction based on the results of the Rank Spearman correlation coefficient of 0,759 and from the results of the coefficient of determination is it known that work environment has a positive relationship with a value of r2 = 66,1%. Hypothesis test results in tcount>ttable (10,292>1,664), Ho is rejected and Ha is accepted